PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI MELALUI DISIPLIN KERJA DI CABANG DINAS PENDIDIKAN WILAYAH PROBOLINGGO - Hartono, Hartono (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
Every government agency has goals to be achieved by utilizing the human resources owned and managed effectively and efficiently, the human resources owned are required to work professionally, have good motivation, good work culture, good work discipline and good performance. This research aims to determine the influence of motivation, work culture and work discipline on employee performance at the Probolinggo Regional Education Office Branch. Data collection methods by distributing questionnaires, documentation and collecting primary and secondary data. The population and sample of this research were employees of the Probolinggo Regional Education Office Branch totaling 32 respondents. Hypothesis testing in this research uses validity test analysis, reliability test and path analysis test. This research data analysis is assisted by the SmartPLS 4.1.0.6 application. The results of this research show that motivation has no significant effect directly on employee performance. Work culture has no significant effect directly on employee performance. Motivation has a significant effect directly on work discipline. Work culture has no significant effect directly on work discipline. Work discipline has no significant effect directly on employee performance. Motivation has no significant indirect effect on employee performance through work discipline. Work culture has no significant indirect effect on employee performance through work discipline.